Determinação de hidrocarbonetos policíclicos aromáticos (HPAs) em mexilhão empregando o método QuEChERS e HPLC-FD - Demarco, Marisa (2017)
The consumption of fish and seafood is considered an important element of a balanced diet. The mussel is a bivalve mollusk which is fed by filtration of organic particles present in suspension in water. In recent years, several issues related to its consumption have arisen due to the risk of exposure to contaminants. Polycyclic aromatic hydrocarbons (PAHs) are organic pollutants formed naturally or by anthropogenic action due to the incomplete combustion of organic matter, etc. These compounds are included in the priority list of pollutants of the European Union and the United States Environmental Protection Agency (USEPA) because of their mutagenic and carcinogenic properties. Since these animals can be exposed to contaminants, these organisms have been reported as an important route of human exposure. The determination of HPAs in food samples is a challenge due to the complexity of the sample and the low levels of concentration of these compounds. The aim of this work was to evaluate the extraction method based on the QuEChERS method to determine seven HPAs (phenanthrene, anthracene, pyrene, chrysene, benzo[k]fluoranthene, benzo[a]pyrene and dibenzo[a,h]anthracene) in mussels. The parameters that affect the extraction efficiency were studied and after the best extraction conditions were found they were validated. The determination by high performance liquid chromatography with fluorescence detection (HPLC-FD) allowed the performance of the analyzes with high selectivity and detectability. The proposed method for the determination of the seven HPAs was validated, and the limits of detection (LOD) and quantification (LOQ) of the method were 0.6 and 2 μg kg-1, respectively. The recovery percentages were between 78 and 114% with RSD ≤ 10%. This method was used to determine PAHs in 20 mussel samples. The sum of the concentrations obtained in each sample ranged from 25.6 to 38.5 μg kg-1. Considering the results obtained, the proposed method proved to be adequate for determination of HPA in mussels as it conferred sufficient selectivity and detectability, and all validated parameters were satisfactory.